Cultivating Characteristic Critical Thinking: Exploring Critical Thinking Abilities through the CBL Learning Model - Har, Besse Harnanengsi; Arsyad, Nurdin; Rusli, (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to explore students' critical thinking abilities through the CBL (Character-Based Learning) learning model which focuses on character development. This research uses a qualitative descriptive method with a case study design. The research subjects were class XI students at SMA Negeri 11 Wajo who took CBL lessons in Mathematics. Data was collected through tests, observations, interviews and document analysis. The research results show that the CBL learning model is able to improve students' critical thinking skills in the aspects of analysis, interpretation and evaluation. Apart from that, the CBL learning model has also proven effective in cultivating student characters such as responsibility, cooperation and independence.